Analogous analogies? Thomas Aquinas and Karl Barth - Furry, Timothy J. (2010)
This article attempts to show that Karl Barth and Thomas Aquinas are not as divergent as often thought. Taking Eugene Rogers's argument as a working hypothesis, I argue for two points of convergence between Barth and Aquinas, specifically on their understandings of analogy. First, both root analogy in christology. Using Christ as the great magister, Aquinas shows how Christ teaches us to see him, despite its difficulty, in his trinitarian divinity. Barth, using the imagery of the prodigal son, discusses how the incarnation places humanity in an ontological relationship within God's own dialogue within the Trinity. Second, both understand analogy as a theological practice, not a metaphysical mechanism or abstract doctrine, though metaphysics and doctrine are at play in their work. Both Aquinas and Barth attempt to train their readers in the judgement necessary to speak truthfully about God. This analogical relationship between Barth and Aquinas I call the analogia Christi.